FESTIVAL PEH CUN : PESTA MUSIM KEMARAU MASYARAKAT TIONGHOA DI KOTA TANGERANG - Lelly Qodariah; Melinda Rahmawati (Haluan Sastra Budaya, 2021)
The purpose of this research is to know a series of activities in Peh Cun Festival and the meaning of each procession carried out. The festival which is celebrated by Chinese Society in Tangerang has its own cultural and historical values. The Method used in this research is Explanative Qualitative Method with a generative approach that gives a detailed identification of a series of Peh Cun Festival celebrated by the Chinese Society and the meaning of the activity. This research used literature study analysis by comparing and studying several literacies such as textbooks, scientific journals and others related to Peh Cun Festival and the meaning of each process carried out. The results of this research are describes of a series of activities and meanings from the holding of the Peh Cun Festival. The conclusion of this research is The Peh Cun Festival is a summer festival celebrated by the Chinese Society with its own significance preserved as cultural heritage.